THE EFFECT OF GROUP COUNSELING SERVICES BY USING TO OVERCOME THE INDEPENDENCE OF STUDENTS IN SD NEGERI 050761 SEI BILAH - Khairina Ulfa Syaimi; Nila Lestari (SENSEI RESEARCH CENTER, 2021)
This study aims to determine the effect of group counseling services to overcome independence in students of SD Negeri 050761 Sei Bilah. The research method used is an experimental method, namely the between-groups design model pretest-posstest control group design. The experimental group received 5 sessions of treatment, which was held once a day. The control group did not get any treatment. The population in this study were students of SD Negeri 050761. The technique used by researchers is non-probability sampling with purposive sampling. Students who became the sample in this study were 20 students with low independence scores consisting of 10 people in the experimental group and 10 in the control group. The instrument used in determining the sample of this study was the independence instrument with four options on the Likert scale. In terms of statistical data analysis techniques using descriptive statistics using the empirical mean to be able to see the average pretest and posttest scores in the group given the treatment, namely the experimental group and the group not given the treatment, namely the control group. Researchers' hypothesis testing used the Wilcoxon signed rank test, comparing the gain scores of the posttest and pretest in the experimental group and the control group.